Manajemen Pembelajaran Guru PAI dalam Mendukung Partisipasi Belajar Siswa pada Pembelajaran Al-Qur’an Hadits di MIN 22 Hulu Sungai Utara - Falhi Azmi; Norlena (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Learning management plays an important role in building an efficient and comfortable learning environment. However, in its implementation, various challenges are still encountered, such as inadequate material preparation, the selection of less varied learning methods, and limited learning aids, which have an impact on low student understanding, especially in the subject of the Qur'an Hadith. This study aims to describe learning management in teaching the Qur'an Hadith along with its supporting and inhibiting factors. The study was conducted at MIN 22 Hulu Sungai Utara with the subject of research teachers of the Qur'an Hadith, as well as additional sources of information from students and the school. Data were collected through observation, interviews, and documentation, then analyzed using qualitative descriptive methods. Data validity was tested using triangulation techniques. The results of the study indicate that the learning management of Islamic Religious Education teachers in supporting student learning participation in learning the Qur'an Hadith is implemented through four main aspects, namely preparation of learning materials, provision of facilities and infrastructure, classroom arrangement, and creation of a conducive learning atmosphere and conditions. These four aspects have been proven to play a role in encouraging student learning participation, which is reflected in their active involvement in the learning process. However, there are still challenges in the form of limited facilities and a limited variety of learning methods. With good learning management, student participation can be more optimally supported. Keywords: Learning Management, Student Learning Participation, Al-Qur'an Hadith Abstrak Manajemen pembelajaran memiliki peranan penting dalam membangun lingkungan belajar yang efisien dan nyaman. Namun, dalam pelaksanaannya masih ditemukan berbagai tantangan, seperti persiapan materi yang kurang memadai, pemilihan metode pembelajaran yang kurang bervariasi, serta keterbatasan alat bantu belajar, yang berdampak pada rendahnya pemahaman siswa, khususnya pada mata pelajaran Al-Qur'an Hadits. Penelitian ini bertujuan untuk mendeskripsikan manajemen pembelajaran dalam pengajaran Al-Qur'an Hadits beserta faktor-faktor pendukung dan penghambatnya. Penelitian dilaksanakan di MIN 22 Hulu Sungai Utara dengan subjek penelitian guru mata pelajaran Al-Qur'an Hadits, serta sumber informasi tambahan dari siswa dan pihak sekolah. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan metode deskriptif kualitatif. Validitas data diuji dengan teknik triangulasi. Hasil penelitian menunjukkan bahwa manajemen pembelajaran guru PAI dalam mendukung partisipasi belajar siswa pada pembelajaran Al-Qur'an Hadits dilaksanakan melalui empat aspek utama, yaitu persiapan materi pembelajaran, penyediaan sarana dan prasarana, pengaturan ruang kelas, serta penciptaan suasana dan kondisi belajar yang kondusif. Keempat aspek tersebut terbukti berperan dalam mendorong partisipasi belajar siswa, yang tercermin dari keterlibatan aktif mereka dalam proses pembelajaran. Meskipun demikian, masih terdapat kendala berupa keterbatasan sarana dan minimnya variasi metode pembelajaran. Dengan pengelolaan pembelajaran yang baik, partisipasi belajar siswa dapat didukung secara lebih optimal. Kata Kunci: Manajemen Pembelajaran, Partisipasi Belajar Siswa, Al-Qur’an Hadits